Liposarcoma of the Spermatic Cord: A Rare Entity - Fazl Qadir Parray; Rayees Ahmad Dar; Nisar Ahmad Chowdri; Arif Hamid; Rayees Ahmed Malik (Case Reports in Urology)
Primary malignant tumours of spermatic cord are rare. The liposarcoma of spermatic cord is a rare entity and only a few cases have been reported in the literature. We report a case of forty five-year-old male with huge left inguinoscrotal swelling. Fine needle aspiration cytology (FNAC) of swelling revealed the diagnosis of a liposarcoma. The patient was subjected to radical orchidectomy and wide excision. Histopathological examination (HPE) of the resected specimen reported a well-differentiated liposarcoma of the spermatic cord and confirmed the diagnosis.